Genomic and phylogenetic analysis of Salmonella enterica serovar Enteritidis strains linked to multiple outbreaks in Brazil. (15th December 2022) - Cao, Guojie; Balkey, Maria; Jin, Qing; Brown, Eric; Allard, Marc; de Melo, Adma Nadja Ferreira; de Souza Pedrosa, Geany Targino; de Oliveira, Tereza Cristina Rocha Moreira; Magnani, Marciane; Macarisin, Dumitru
Abstract: Salmonella enterica subsp. enterica serovar Enteritidis (SE) has become the prevalent serovar isolated from gastroenteritis cases in Brazil since the 1990's. To better understanding about the genomic diversity and phylogenetic relationship amongst SE epidemic isolates from Brazil, 30 SE isolates from a variety of implicated foods and case patients of outbreaks between 1999 and 2006 were selected for genome comparison analyses. SE genomes were also compared against publicly available Brazilian SE isolates from pre- and post-epidemic period. MLST analysis revealed that all isolates belong to sequence type (ST) 11. Seven Salmonella pathogenicity islands (SPIs) (SPI-1, SPI-3 to 5, SPI-13, SPI14, and C63PI) were identified in the evaluated genomes and all studied SE genomes carried similar prophage profiling. Resistome analysis revealed the presence of resistance genes to aminoglycosides [ aac(6')laa, aph(3")-lb, aph(6)-ld], as well as point mutations in gyrA . Phylogenetic analysis demonstrated that certain isolates have circulated in Brazil for years and been involved in distinct outbreaks.